Bi-level Programming of Park Energy Internet Considering Economy and Security. Issue 1 (November 2020) - Suchun, FAN; Zhang, Yongjun
Abstract: Park energy Internet is an important research and development direction catering to the requirements of energy sustainability. In this paper, a typical structure of park energy Internet and models of several energy equipment are built. Multiple evaluation indexes including overall energy utilization rate, overall energy self-sufficiency rate and energy shortage expectation are proposed. Based on this, a bilevel programming model of park energy Internet considering economy and security is proposed. Further, a hybrid solving strategy of cataclysmic genetic algorithm and CPLEX solver is used to reduce the time of solution and improve the convergence. Finally, it is proved that the proposed method can meet the requirements of the economy and security of the system as well as the energy sustainability.